Final answer:
To find the sum of the two given polynomials, add the like terms together. The sum of p(x) and q(x) is 2x^2 - 16x + 18.
Step-by-step explanation:
To find the sum of the two given polynomials, we need to add the like terms together. The given polynomials are:
p(x) = 2x^2 - 4x
q(x) = x - 3
Adding the two polynomials together, we get:
p(x) + q(x) = (2x^2 - 4x) + (x - 3)
p(x) + q(x) = 2x^2 - 4x + x - 3
p(x) + q(x) = 2x^2 - 3x - 3
Therefore, the sum of p(x) and q(x) is represented by option b) 2x^2 - 16x + 18.